2D graphene-coupled ZnS:Mn2+ mechanodetectors for monitoring the pulse rate. Issue 10 (July 2020) - Zheng, Zhiqin; Zhao, Jun; Jin, Dingfeng; Wang, Xinxing
Abstract: In this work, we prepared a type of traditional mechanoluminescent (ML) material ( i.e., ZnS:Mn 2+ ) by using the sol-gel method with addition of K2 S to the Zinc Oleate and Mn(NO3 )2 water solution. Then, 2D graphene-coupled ZnS:Mn 2+ nanocomposites were achieved by coupling the ZnS:Mn 2+ with the 2D graphene. All the samples were characterized using powder X-ray diffraction (XRD), transmission electron microscopy (TEM), photoluminescence (PL) and pressure-induced PL spectra, galvanostatic charge-discharge and cyclic voltammetry. The PL results indicated that the ZnS:Mn 2+ and 2D graphene-coupled ZnS:Mn 2+ samples exhibited a broad Mn 2+ emission band at 585 nm. The pressure-induced PL spectra showed that the two samples had pressure-controlled luminescence. The pressure-induced PL positions were the same as the PL positions. Since the ML properties are related to the defects, here we added the Li + ions into the ZnS:Mn 2+ sample in order to study the influence of defects on the ML spectral variation, where the Li + ions were used as the charge compensator. As a result, a mechanistic profile which could illustrate the ML reason was proposed. When the conductive polyoxometalate (POM) was dispersed into the ZnS:Mn 2+ and graphene-coupled ZnS:Mn 2+, we found further that the ML intensity and the used pressure value featured a linear relationship and the ML intensity of the two samples could recover after several cycles. Finally, we demonstrated that the graphene-coupled ZnS:Mn 2+ could use for monitoring human health problem such as the pulse rate.